2013
DOI: 10.1155/2013/847672
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Minimal Residual Disease by Flow Cytometry for Patients with Multiple Myeloma Submitted to Autologous Hematopoietic Stem Cell Transplantation

Abstract: The treatment strategy in multiple myeloma (MM) is to get complete remission followed by high-dose chemotherapy and autologous Hematopoietic Stem Cell Transplantation (HSCT). Neoplastic Plasma Cells (NPCs) are CD45−/dim, CD38+high, CD138+, CD19−, and  CD56+high in most cases. The description of this immunophenotype is of major importance as it leads to the correct identification of minimal residual disease (MRD). Samples from 44 Patients were analyzed prospectively in this study. We analyzed if the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Multiparameter flow cytometry (MFC) (four or more colors) is frequently applied in clinical practice for the detection of MRD [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and although its sensitivity (approximately 10 −4 ) is inferior to that of the allele-specific oligonucleotide-PCR (ASO-PCR) assay, there is little difference between the clinical values of these methods [ 15 ]. Previous IMWG criteria define immunophenotypic CR (iCR) as stringent CR (sCR), in which MRD is not detected by MFC [ 23 ].…”
Section: Mrd Detection Methodsmentioning
confidence: 99%
“…Multiparameter flow cytometry (MFC) (four or more colors) is frequently applied in clinical practice for the detection of MRD [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and although its sensitivity (approximately 10 −4 ) is inferior to that of the allele-specific oligonucleotide-PCR (ASO-PCR) assay, there is little difference between the clinical values of these methods [ 15 ]. Previous IMWG criteria define immunophenotypic CR (iCR) as stringent CR (sCR), in which MRD is not detected by MFC [ 23 ].…”
Section: Mrd Detection Methodsmentioning
confidence: 99%
“…8,1214,1618,24,25,2831 The impact of MRD status on OS was assessed in 12 studies involving 1,100 patients (599 MRD-negative, 501 MRD-positive). 6,8,13,14,1619,24,25,28,31 Compared with MRD positivity, MRD negativity was associated with better PFS (HR 0.41; 95% CI 0.36–0.48; P < .0001) (Figure 2A) and OS (HR 0.57; 95% CI 0.46–0.71; P < .0001) (Figure 2B). Median PFS was 54 months for MRD-negative patients and 26 months for MRD-positive patients (Figure 2C); median OS was 98 and 82 months, respectively (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…1214,1618,29,30 One study found no significant difference in outcomes between patients with or without detectable MRD. 14 Others noted that MRD status did not correlate with standard response criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations